Ultrastructure Study of Hydatid Cyst Isolated from Sheep Exposure to Tendazol and Bendaziole (Medico Legal Update, 2020)
Cystic Echinococcosis is the most important zoonotic parasite with community health in addition to financialproblem. This study was planned to detect a morphological structure of protoscolices of hydatid cysts thatisolated from slaughtered sheep that exposure to Tinidazole and Bendaziole, and showed a different numberand shape of hydatid cysts from different organs like; lungs and livers, with viability result of protoscolices.A clear be to found a hydatid sand and protoscolices distribution, and germinal layer without any treatment,all normal in shape and structure, but samples treated with drug Tinidazole and Bendaziole. It is a clearfound distraction of protoscolices, and germinal layer of hydatid cyst in shape and structure. The currentstudy explain some different between the liquid and germinal layer of cyst when sample treated with thesedrugs and other not treated in shape and morphological form of protoscolices.